PENERAPAN DATA MINING MENGGUNAKAN ALGORITMA APRIORI UNTUK MENENTUKAN MENU MAKANAN BERGIZI GRATIS - Masesa Angga Wijaya; Meinawati (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2026)
The free nutritious meal program is a government initiative to improve public health and reduce stunting in Indonesia. However, planning daily combinations that balance nutrition, variety, and recipient preferences remains a challenge. This study applies data mining techniques using the Apriori Algorithm to discover optimal food menu combinations based on functional nutritional standards. The data analyzed includes historical food distribution records, nutritional content, and consumer satisfaction. Through data preprocessing and setting minimum support and confidence thresholds, strong association rules between food items were identified. The results demonstrate that the Apriori Algorithm successfully extracts significant patterns; for instance, a menu containing